Method for preparing nano cerium oxide through supergravity reinforcement
By premixing cerium chloride solution and ammonia water in a supergravity reactor, the problems of uneven nano cerium oxide particle size and low production efficiency in the prior art are solved, and high-efficiency, low energy consumption and environmentally friendly nano cerium oxide preparation are achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411850456.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art has problems such as uneven particle size, easy pollution, high cost, low production efficiency and environmental pollution when preparing nano cerium oxide, making it difficult to achieve efficient, low energy consumption and environmentally friendly industrial production.
Using supergravity strengthening technology, nano cerium oxide is obtained by premixing cerium chloride solution and ammonia water in a supergravity reactor to form a mixed slurry, and then suction filtration, washing, drying and high-temperature oxidation and calcination.
The production efficiency is significantly improved, the nano cerium oxide prepared has a small particle size, narrow distribution, high crystallinity, and no need to add modifiers, which reduces costs and avoids environmental pollution, making it suitable for large-scale industrial production.
Smart Images

Figure CN119528201A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano rare earth material preparation, and in particular relates to a method for preparing nano cerium oxide by ultra-gravity enhancement. Background Art
[0002] my country is rich in rare earth resources. Rare earth metals and rare earth alloys in new rare earth materials are widely used in petrochemicals, automobile industry, aerospace, optical devices and other fields. Among my country's rare earth resources, cerium has the highest distribution content. The full development and utilization of cerium resources has important practical significance for my country's production and economy. As a cheap and widely used light rare earth, cerium oxide is widely used in petrochemicals, polishing materials, automobile exhaust purification, special glass, ceramics, etc. For example, the polishing powder prepared by cerium oxide can significantly improve the polishing efficiency and polishing effect of silicon wafers; adding it to ceramic formula can reduce the sintering temperature of ceramics and increase its density; loading it on catalysts can effectively regulate the geometry and electronic effects of catalysts and improve catalytic performance. With the increasing requirements of scientific and technological development, rare earth materials are developing in the direction of nano-crystalization, requiring cerium oxide to have the characteristics of small particle size and narrow distribution. Therefore, it is necessary to explore the process of producing nano cerium oxide with high efficiency, low energy consumption and environmental protection, make full use of the value of cerium resources, and help solve the problem of oversupply of cerium elements.
[0003] At present, the preparation of nano-cerium oxide generally adopts ball milling, spray thermal decomposition, microemulsion, sol-gel, hydrothermal and other methods. The ball milling process is simple and low in cost, but the obtained powder has uneven particle size, serious particle agglomeration and is easily contaminated. The spray thermal decomposition method is simple to operate, but there are individual hollow particles and broken spherical shells in the powder. The powders prepared by the sol-gel method and microemulsion method have high purity, uniform particle size and high chemical activity, but the raw material cost is high, the production efficiency is low, and it is difficult to achieve industrial large-scale production. Although the hydrothermal method can prepare nano-cerium oxide with controllable morphology and particle size, the additives such as surfactants, dispersants and template agents used in the production process will cause pollution to the environment. Therefore, it is of great significance to develop a green and efficient technology for producing nano-cerium oxide.
[0004] Supergravity technology is a breakthrough technology that strengthens the micro-mixing and mass transfer of chemical processes through high-speed rotary shearing. Compared with traditional stirring, it can significantly improve the mass transfer efficiency. It has the advantages of small equipment size and light weight, low process energy consumption, easy engineering scale-up, large production capacity and strong adaptability. As a strengthening technology, it has been widely used in the chemical industry. Under supergravity conditions, the nucleation process is carried out in a micro-uniform environment, making the nucleation process controllable, and the supergravity field mixing performance is excellent, so that nano-powder materials with controllable morphology, uniform particle size and stable performance can be obtained, and the mixing time is short, which does not affect the subsequent formation of nano-materials based on crystal nuclei. Therefore, the supergravity technology is applied to the process of preparing nano-cerium oxide, replacing the traditional stirred reactor, significantly improving the mass transfer efficiency and production efficiency between the liquid phase, and producing nano-cerium oxide powders with small particle size and uniform dispersion, which is easy to promote and apply to industrial production. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing nano cerium oxide by ultra-gravity enhancement; the method of the present invention can improve production efficiency, the prepared nano cerium oxide has a small particle size and a narrow particle size distribution, and the crystallinity is improved.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing nano-cerium oxide by ultra-gravity enhancement comprises the following steps:
[0008] 1) dissolving the cerium source cerium chloride hexahydrate completely with deionized water to prepare a cerium chloride solution;
[0009] 2) at room temperature, the cerium chloride solution is input into the high gravity reactor through a peristaltic pump, and then the ammonia water is input into the high gravity reactor through a horizontal flow pump, and a mixed slurry is formed after premixing reaction in the high gravity reactor;
[0010] 3) After the premixing reaction is completed, the mixed slurry is taken out, filtered, washed, dried and subjected to high-temperature oxidation calcination to obtain nano cerium oxide.
[0011] Preferably, in step 1), the concentration of the cerium chloride solution is 0.2-0.7 mol / L.
[0012] Preferably, in step 2), the amount of ammonia water added is until the pH value of the mixed slurry reaches 9-12.
[0013] Preferably, in step 2), the rotor speed in the ultragravity reactor is 300-3000 r / min, preferably 2000-2850 r / min.
[0014] Preferably, in step 2), the feed flow rate of the cerium chloride solution is 30-50 L / h.
[0015] Preferably, in step 2), the feed flow rate of the aqueous ammonia is 1-10 L / h.
[0016] Preferably, in step 2), the mixed slurry is circulated in the high gravity reactor 25-50 times.
[0017] Preferably, in step 2), the premixing reaction time is 0.5-2h.
[0018] Preferably, in step 3), the washing is performed by alternating washing with ethanol and deionized water, and the number of washing times for each washing is 3-6 times.
[0019] Preferably, in step 3), the drying is oven drying, the oven drying temperature is 60-80° C., and the time is 3-12 h.
[0020] Preferably, in step 3), the temperature of the high temperature oxidation calcination is 500-700° C., and the calcination time is 1-2 h.
[0021] Any range described in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0022] Unless otherwise specified, all raw materials in the present invention can be purchased from the market, and the equipment used in the present invention can adopt conventional equipment in the relevant field or refer to the existing technology in the relevant field.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention provides a method for preparing nano-cerium oxide by ultra-gravity enhancement, which has high production efficiency, does not require a modifier and has high product quality. Combined with the characteristics of ultra-gravity enhanced mass transfer, the prepared product has high crystallinity (90-96%), small particle size (14-20nm) and uniform particle size distribution (5-40nm), which is energy-saving, production-increasing and quality-improving for the industrial production of nano-cerium oxide.
[0025] 2. The present invention uses deionized water as a solvent, and the production process is safe and reliable; no surface modifier is needed to be added, which reduces the cost of raw materials and avoids the pollution of the surface modifier to the product and the environment.
[0026] 3. The present invention obtains the process conditions for synthesizing nano-cerium oxide with narrow distribution and controllable particle size by changing the precipitant, reaction time, circulation flow, motor speed and calcination conditions. The equipment is small in size, simple in operation, safe and reliable, and can be easily promoted to large-scale industrial production. The obtained nano-cerium oxide can be used for molecular sieve loading to improve catalyst performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0028] Figure 1 The experimental flow chart of the preparation method of the present invention is shown. DETAILED DESCRIPTION
[0029] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0030] The cerium chloride in the embodiment of the present invention was purchased from the high-purity cerium chloride hexahydrate product produced by Shanghai Aladdin Biochemical Technology Co., Ltd., the ammonia water was purchased from the analytical grade ammonia water product produced by Beijing Inokai Technology Co., Ltd., the cerium nitrate hexahydrate in the comparative example was purchased from the chemically pure cerium nitrate hexahydrate product produced by Shanghai McLean Biochemical Technology Co., Ltd., and the methanol was purchased from the chemically pure methanol product produced by Xilong Science Co., Ltd.
[0031] The supergravity device used in the present invention is a prior art, such as the supergravity device disclosed in CN107684880A, such as the supergravity device disclosed in CN118204047A.
[0032] As one aspect of the present invention, a method for preparing nano-cerium oxide by ultra-gravity enhancement comprises the following steps:
[0033] 1) dissolving the cerium source cerium chloride hexahydrate completely with deionized water to prepare a cerium chloride solution;
[0034] 2) at room temperature, the cerium chloride solution is input into the high gravity reactor through a peristaltic pump, and then the ammonia water is input into the high gravity reactor through a horizontal flow pump, and a mixed slurry is formed after premixing reaction in the high gravity reactor;
[0035] 3) After the premixing reaction is completed, the mixed slurry is taken out, filtered, washed, dried and subjected to high-temperature oxidation calcination to obtain nano cerium oxide.
[0036] The principle of the preparation method of the present invention is as follows:
[0037] The present invention uses ammonia water as a precipitant and cerium chloride hexahydrate as a cerium source precursor. With the help of a hypergravity field, the microscopic mixing and mass transfer characteristics are enhanced, the mass transfer process of rapid precipitation is significantly enhanced, and the contact possibility and contact efficiency of cerium chloride and hydroxide ions provided by ammonia water are enhanced, thereby accelerating the precipitation reaction, and making the precipitation particles generated by the contact reaction quickly and evenly dispersed, thereby reducing the agglomeration of particles under the condition of high raw material concentration; the huge shear force generated by the rotation of the wire mesh filler in the hypergravity rotating bed causes the precipitation particles to collide with the sieve holes, thereby controlling the crystal form to a certain extent, and obtaining grains with controllable morphology, small particle size and uniformity. Secondly, the present invention uses deionized water as a solvent to achieve rapid homogeneous precipitation under a hypergravity field, avoiding the safety hazards caused by the volatility and flammability of non-polar solvents (such as methanol, methyl ether, etc.). Ammonia water is used as a precipitant to first generate Ce(OH)3 precipitation, which is oxidized to hydrated Ce in an alkaline environment. 4+ , further hydrolyzed to form [Ce(OH) x (H2O) y ] (4-x)+ Complex, Ce 4+ High charge, small radius, and small precipitation core during the precipitation process are one of the more important conditions for preparing nanopowders. The ultra-gravity reactor is then used to strengthen the premixing characteristics and accelerate Ce 3+ Oxidized to Ce 4+ , improve the precipitation efficiency, and finally through high-temperature oxidation calcination, deprotonate the water molecules of cerium hydroxide hydrate to form cerium oxide, and improve its purity and crystallinity to obtain nano cerium oxide with small particle size and uniform distribution.
[0038] According to some embodiments of the present invention, in step 1), the concentration of the cerium chloride solution is 0.2-0.7 mol / L.
[0039] According to certain embodiments of the present invention, in step 2), the amount of ammonia water added is until the pH value of the mixed slurry reaches 9-12.
[0040] According to certain embodiments of the present invention, in step 2), the rotor speed in the ultragravity reactor is 300-3000 r / min, preferably 2000-2850 r / min.
[0041] According to some embodiments of the present invention, in step 2), the feed flow rate of the cerium chloride solution is 30-50 L / h.
[0042] According to certain embodiments of the present invention, in step 2), the feed flow rate of the aqueous ammonia is 1-10 L / h.
[0043] According to certain embodiments of the present invention, in step 2), the mixed slurry is circulated in the high gravity reactor 25-50 times.
[0044] According to certain embodiments of the present invention, in step 2), the premixing reaction time is 0.5-2h.
[0045] According to some embodiments of the present invention, in step 3), the washing is performed by alternating washing with ethanol and deionized water, and the number of washing times for each washing is 3-6 times.
[0046] According to some embodiments of the present invention, in step 3), the drying is oven drying at a temperature of 60-80° C. for a time of 3-12 h.
[0047] According to some embodiments of the present invention, in step 3), the temperature of the high temperature oxidation calcination is 500-700° C., and the calcination time is 1-2 h.
[0048] Example 1
[0049] A method for preparing nano-cerium oxide by ultra-gravity enhancement comprises the following steps:
[0050] Prepare 0.63 mol·L with 500 mL of deionized water -1 The hexahydrate cerium chloride solution is prepared by a peristaltic pump at a flow rate of 50 L / h, and then ammonia water is fed by a horizontal flow pump at a flow rate of 5 L / h, and the pH of the mixed liquid is added to 10. The reaction is carried out under the condition of a supergravity speed of 2850 r / min, a circulation volume of 60 L / h, and the reaction is carried out at room temperature for 1 hour. After the reaction is completed, the product is taken out and filtered, and washed with ethanol and deionized water for 3 times each to obtain a filter cake, which is placed at 60°C and dried for 12 hours, and then calcined at 600°C for 1 hour to obtain nano cerium oxide. The average particle size is measured to be about 18.5 nm, the particle size distribution range is 5-40 nm, and the crystallinity is about 93.4%.
[0051] Example 2
[0052] A method for preparing nano-cerium oxide by ultra-gravity enhancement comprises the following steps:
[0053] Prepare 0.63 mol·L with 500 mL of deionized water -1Hexahydrate cerium chloride solution is fed in two streams. The cerium source is first fed by a peristaltic pump at a flow rate of 50L / h, and then ammonia water is fed by a horizontal flow pump at a flow rate of 1L / h, and the pH of the mixed liquid is added to 10. The reaction is carried out under the condition of a supergravity speed of 2850r / min, a circulation volume of 100L / h, and the reaction is carried out at room temperature for 0.5h; after the reaction is completed, the product is taken out and filtered, and washed with ethanol and deionized water for 3 times each to obtain a filter cake, which is placed at 60°C and dried for 3-12h, and then calcined at 650°C for 1.5h to obtain nano-cerium oxide, which is in the form of spherical particles. The average particle size is measured to be about 16.6nm, the particle size distribution range is 6-28nm, and the crystallinity is about 91.1%.
[0054] Example 3
[0055] A method for preparing nano-cerium oxide by ultra-gravity enhancement comprises the following steps:
[0056] Prepare 0.20 mol·L with 500 mL of deionized water -1 Hexahydrate cerium chloride solution is fed in two streams, the cerium source is first fed at a flow rate of 30L / h, and then ammonia water is fed at a flow rate of 2L / h by a horizontal flow pump, and the pH of the mixed liquid is added to 9, and the reaction is carried out under the condition of a supergravity speed of 2000r / min, a circulation volume of 60L / h, and the reaction is carried out at room temperature for 0.5h; after the reaction is completed, the product is taken out and filtered, and washed with ethanol and deionized water for 3 times each to obtain a filter cake, which is placed at 60°C and dried for 6h, and then calcined at 600°C for 1h to obtain nano cerium oxide, and its average particle size is measured to be about 15.6nm, the particle size distribution range is 7-25nm, and the crystallinity is about 95.2%.
[0057] Example 4
[0058] A method for preparing nano-cerium oxide by ultra-gravity enhancement comprises the following steps:
[0059] Prepare 0.32 mol·L with 500 mL of deionized water -1 Hexahydrate cerium chloride solution is fed in two streams, the cerium source is first fed at a flow rate of 30L / h, and then ammonia water is fed at a flow rate of 1L / h by a horizontal flow pump, and the pH of the mixed liquid is added to 9, and the reaction is carried out under the condition of a supergravity speed of 2400r / min, a circulation volume of 50L / h, and the reaction is carried out at room temperature for 2h; after the reaction is completed, the product is taken out and filtered, and washed with ethanol and deionized water for 3 times each to obtain a filter cake, which is placed at 60°C for 10h and then calcined at 650°C for 1h to obtain nano cerium oxide, and its average particle size is measured to be about 18.4nm, the particle size distribution range is 10-35nm, and the crystallinity is about 91.1%.
[0060] Example 5
[0061] A method for preparing nano-cerium oxide by ultra-gravity enhancement comprises the following steps:
[0062] Prepare 0.32 mol·L with 500 mL of deionized water -1 Hexahydrate cerium chloride solution is fed in two streams, the cerium source is first fed at a flow rate of 50L / h, and then ammonia water is fed at a flow rate of 2L / h by a horizontal flow pump, and the pH of the mixed liquid is added to 10, and the reaction is carried out under the condition of a supergravity speed of 2850r / min, a circulation volume of 70L / h, and the reaction is carried out at room temperature for 0.5h; after the reaction is completed, the product is taken out and filtered, and washed with ethanol and deionized water for 3 times each to obtain a filter cake, which is placed at 60°C and dried for 12h, and then calcined at 600°C for 1h to obtain nano cerium oxide, which is in the form of spherical particles. The average particle size is measured to be about 14.8nm, the particle size distribution range is 9-28nm, and the crystallinity is about 94.6%.
[0063] Comparative Example 1
[0064] The same as Example 1, except that the premixing is carried out in a traditional stirred tank at room temperature at a stirring speed of 500 r / min for 0.5 h. After the same filtering, washing, drying and calcining treatments, the average particle size of the product is 28.6 nm, the particle size range is 14-55 nm, and the crystallinity is as low as 88.7%.
[0065] It can be seen that at high cerium source concentrations, the particle dispersion effect in the traditional stirred tank is worse, resulting in an overall larger particle size and reduced crystallinity.
[0066] Comparative Example 2
[0067] The same as Example 5, except that the premixing is carried out in a traditional stirred tank at room temperature at a stirring speed of 500 r / min for 2 hours. After the same filtering, washing, drying and calcining treatments, the average particle size of the product is 18.3 nm, the particle size range is 12-25 nm, and the crystallinity is as low as 88.2%.
[0068] It can be seen that the particle dispersion effect in the traditional stirred tank is poor, which will lead to larger particle size and poor material mixing effect, resulting in low crystallinity of cerium oxide generated by the reaction and low overall preparation efficiency.
[0069] Comparative Example 3
[0070] The same as Example 1, except that the calcination temperature was increased to 850°C. After the same treatment process, the nano-cerium oxide had an average particle size of 21.3 nm, a particle size range of 5-44 nm, and a crystallinity of about 95.4%.
[0071] It can be seen that if the calcination temperature is too high, the cerium oxide grains will grow larger and the agglomeration phenomenon will become more serious.
[0072] Comparative Example 4
[0073] The same as Example 2, except that the solvent was changed to methanol, and after the same premixing, filtering, washing, drying and calcining treatments, the average particle size of the product was 18.7 nm, the particle size range was 8-27 nm, and the crystallinity was about 92.2%.
[0074] It can be seen that the results obtained using methanol as solvent and deionized water as solvent are not much different, but methanol is highly volatile and easily evaporates into the air, causing changes in the concentration of the solution in the experiment, affecting the repeatability and accuracy of the experiment. In addition, methanol is toxic and irritating, so deionized water is the preferred solvent.
[0075] Comparative Example 5
[0076] The same as Example 2, except that the cerium source was changed to cerium nitrate hexahydrate, and after the same filtering, washing, drying and calcining treatments, the average particle size of the product obtained was 20.2 nm, the particle size range was 10-35 nm, and the crystallinity was about 90.8%.
[0077] It can be seen that the results obtained by using cerium nitrate hexahydrate and cerium chloride hexahydrate as cerium sources are not much different, but cerium nitrate hexahydrate is more expensive. Therefore, considering the economy, cerium chloride is preferably used as the cerium source.
[0078] Comparative Example 6
[0079] The same as Example 2, except that the premixing was continued for aging, the premixing was carried out in a supergravity reactor at a speed of 2850 rpm at room temperature for 0.5 h, and then transferred to an oil bath pot at 90° C. for aging for 16 h. After the same filtering, washing, drying and calcining treatment, the nano cerium oxide had an average particle size of 29.5 nm, a particle size range of 5-65 nm, and a crystallinity of about 91.9%.
[0080] It can be seen that the grains further develop and grow during the aging process, but the crystallinity after calcination is not much different from that in the embodiment, and the aging stage can be omitted.
[0081] Comparative Example 7
[0082] The same as Example 5, except that the reaction time was prolonged, and the premixing was carried out in an ultra-gravity reactor at a rotation speed of 2850 rpm at room temperature for 3 hours. After the same filtering, washing, drying and calcining treatments, the average particle size of the nano-cerium oxide obtained after calcination was 16.9 nm, the particle size range was 10-29 nm, and the crystallinity was about 90.1%.
[0083] It can be seen that the increase in reaction time will lead to the development of grains and the engulfment of surrounding grains, thereby growing larger, resulting in an increase in the particle size of the product.
[0084] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A method for preparing nano-cerium oxide by ultra-gravity enhancement, characterized in that: The steps include: 1) dissolving the cerium source cerium chloride hexahydrate completely with deionized water to prepare a cerium chloride solution; 2) at room temperature, the cerium chloride solution is input into the high gravity reactor through a peristaltic pump, and then the ammonia water is input into the high gravity reactor through a horizontal flow pump, and a mixed slurry is formed after premixing reaction in the high gravity reactor; 3) After the premixing reaction is completed, the mixed slurry is taken out, filtered, washed, dried and subjected to high-temperature oxidation calcination to obtain nano cerium oxide.
2. The method for preparing nano-cerium oxide by ultra-gravity enhancement according to claim 1, characterized in that: In step 1), the concentration of the cerium chloride solution is 0.2-0.7 mol / L.
3. The method for preparing nano-cerium oxide by ultra-gravity enhancement according to claim 1, characterized in that: In step 2), the amount of ammonia water added is until the pH value of the mixed slurry reaches 9-12.
4. The method for preparing nano-cerium oxide by ultra-gravity enhancement according to claim 1, characterized in that: In step 2), the rotor speed in the supergravity reactor is 300-3000 r / min, preferably 2000-2850 r / min.
5. The method for preparing nano-cerium oxide by ultra-gravity enhancement according to claim 1, characterized in that: In step 2), the feed flow rate of the cerium chloride solution is 30-50 L / h.
6. The method for preparing nano-cerium oxide by ultra-gravity enhancement according to claim 1, characterized in that: In step 2), the feed flow rate of the ammonia water is 1-10 L / h.
7. The method for preparing nano-cerium oxide by ultra-gravity enhancement according to claim 1, characterized in that: In step 2), the mixed slurry is circulated in the high gravity reactor 25-50 times.
8. The method for preparing nano-cerium oxide by ultra-gravity enhancement according to claim 1, characterized in that: In step 2), the premixing reaction time is 0.5-2h.
9. The method for preparing nano-cerium oxide by ultra-gravity enhancement according to claim 1, characterized in that: In step 3), the washing is performed by alternating washing with ethanol and deionized water, and the number of washing times for each washing is 3-6 times.
10. The method for preparing nano-cerium oxide by ultra-gravity enhancement according to claim 1, characterized in that: In step 3), the drying is oven drying at a temperature of 60-80° C. for 3-12 hours; Preferably, in step 3), the temperature of the high temperature oxidation calcination is 500-700° C., and the calcination time is 1-2 h.
Citation Information
Patent Citations
Hyper-gravity device for enhancing reaction by gas-liquid efficient premixing and application method thereof
CN107684880A
Supergravity system device and method for preparing molecular sieve by one-step method
CN118204047A
Cited By
Preparation method of high-purity nano rare earth oxide powder
CN121063571A
Method for preparing high-purity nanometer rare earth oxide powder
CN121063571B
Preparation method of rare earth zirconate powder for thermal barrier coating
CN121063584A
Preparation method of rare earth zirconate powder for thermal barrier coating
CN121063584B
Preparation method of nano cerium oxide
CN121470531A